Effect of Sb2O3 on the electrical properties of Ba0.9Ca0.1Zr0.1Ti0.9O3 ceramics fabricated using nanocrystals seed - Parjansri P. (2017)
© 2016, Springer-Verlag Berlin Heidelberg. This work was to investigate the effects of antimony oxide (Sb 2 O 3 ) on the electrical properties of Ba 0.9 Ca 0.1 Zr 0.1 Ti 0.9 O 3 (BCZT) ceramics and was prepared by adding 1 mol% of BCZT nanocrystals. The seed is nanocrystals of BCZT which was synthesized by the molten salt method. The ceramics powders were prepared by the mixed oxide method using BaCO 3 , CaCO 3 , ZrO 2 , TiO 2 as starting materials, and the BCZT seed was added as nanocrystal for induce phase transition. They were doped with x mol% Sb 2 O 3 (x = 0.0–0.5). Results indicated that all samples show pure perovskite phase. The Sb 2 O 3 enhanced the electrical properties of the ceramic systems. Excellent values of a dielectric constant (ε r ) at room temperature (T r ) were 4086 with sample of x = 0.5, and at Curie temperature (T c ) was 15,485 for samples with x = 0.1. The highest remnant polarization (P r ), piezoelectric charge coefficient (d 33 ), piezoelectric voltage coefficient (g 33 ), electromechanical coefficient for planar mode (k p ) and thickness mode (k t ) values were 6.3 μC/cm 2 , 346 pC/N, 15.6 × 10 −3  Vm/N, 42 and 41 %, respectively, which were obtained for the sample of x = 0.2 mol% Sb.